Biogas yield from co-digesting banana pseudostems with cow dung: Transitioning from mesophilic to thermophilic regimes - Sooraj Mohan; Augustine B. V. Barboza; K. Ashwini; P. Dinesha (Cogent Engineering)
Biogas is an important renewable energy resource that has been considered as carbon neutral. The advantage that it can also reduce volumes of biowaste makes it an attractive option for secondary source of energy. In this scenario, large amounts of banana wastes are observed around the world with minimum work in anaerobic digestion. Hence, the present study demonstrates the anaerobic digestion of banana pseudo stem (BP) and cow dung (CD) feedstock by co-digesting them in different proportions (5 levels of BP – 0%, 30%, 50%, 70%, and 100%) and varying digester temperatures (3 levels: 42.5 °C, 45 °C, and 47.5 °C). Batch scale 1 liter feedstocks are prepared and digested for a period of 30 days. Initial studies suggested that the optimal temperature for digesting BP is between 40 and 50 °C which falls in the transition of mesophilic and thermophilic range. At all the digester temperatures, pure BP feedstock produced an average of 74% lower biogas as compared to CD feedstock. However, co-digesting CD with about 30% BP had a negligible loss in biogas production (1.2%). Further experimental data was subjected to regression, ANOVA, and optimization analyses. The optimization study results reveal that more than 5000 ml/liter of feedstock can be obtained for BP feedstock within 30-40% proportions if the temperature is maintained between 45 to 47 °C.